Making Your Business Plan a Real One by Establishing Milestones - Kasinath Sastry, K.; H. R., Dilip (Prabandhan: Indian Journal of Management, 2012)
The main aim of any business is to maximize the profit and create wealth for a company. Customer satisfaction and cost of production are the two parameters which are to be dealt, in maximizing the profit and wealth. Cost of production is directly proportionate to the customer satisfaction. Higher the customer, the higher will be the cost. If the customer satisfaction is the main objective, then we may have to compromise on the cost of production and the customer satisfaction. To optimize the customer satisfaction and the cost of production, we have to fix a feasible target for the output of any organization, and then everyone in the organization has to chase and see that their target is attained. To reach these targets, everyone in the organization has to fix his own target and integrate it with that of the organization. This target or the objective of the organization is identified as the milestone of the organization in respect to the output. This paper makes a study in to the different aspects of fixing the target for the company and then passing it on to the different departments and to each activity of every department.